A survey of internal and family medicine residents: Assessment of disability-specific education and knowledge. Issue 2 (April 2021) - Stillman, Michael D.; Ankam, Nethra; Mallow, Michael; Capron, Maclain; Williams, Steve
Abstract: Background: The literature suggests that primary care physicians are inadequately educated in the care of people with disabilities. No study to date has evaluated whether internal medicine (IM) and family medicine (FM) residents have received disability-specific education or their level of comfort in caring for people with physical disabilities. Objectives: To assess IM and FM residents' receipt of disability-specific education during medical school and residency; to evaluate their self-reported comfort in managing secondary conditions associated with physical disabilities and in coordinating therapies and services for individuals with disabilities; to gauge their interest in receiving disability-specific education. Methods: An on-line survey distributed to residents at a convenience sample of ten academic IM and FM residency programs in the northeastern United States. Participants (n = 176) were asked about their socio-demographic and training-specific characteristics and their self-assessed ability to manage secondary conditions associated with physical disabilities and coordinate care and services for individuals with disabilities. Chi Square tests were used to compare participant characteristics and outcomes. Results: Few participants had received disability-specific education during medical school or residency (34.6% and 11.2%, respectively), and nearly all (96.0%) expressed interest in receiving more. Small minorities reported feeling comfortable managing common secondary conditions or in coordinating therapies and services for individuals with disabilities. Conclusion: Although one-fifth of adult Americans have a disability, few of our participating IM and FM residents had received disability-specific education or felt comfortable managing the care of people living with disabilities. Our results indicate a need to develop and disseminate disability-specific curricula.